(3GdMeGjI GdOhdjI ddeHYhKjf GdOHdheGSjjf EHGf GdfRGYGJ GdeSdMI GdOhdjI (B/s - (3YeQ, GdgGOj SGde eMeOs ((3GdLjRI, LeghQjI eUQ GdYQHjI (B:s (3eQcR GdOQGSGJ GdYQHjI ddfTQ hGdJhRjY,s, 2017)
(3jJMOK GdcJGH Yf GdMeGjI GdOhdjI ddeHYhKjf GdOHdheGSjjf EHGf GdfRGYGJ GdeSdMI GdOhdjI MjK OCHJ GdOhd efP GdbOe Ydi GMJQGe GdeHYhKjf GdOHdheGSjjf HGYJHGQge eeKdjf Ohdge hdPG bGeJ HMeGjJge hCSQge heeJdcGJge hPdc dcaGdI bjGege HCYeGdge HYjOG Yf Cj JCKjQ ceG Cf GdOhd hGdTYhH Ydi GNJdGa KbaGJgG QGYJ Ydi eQ GdJGQjN GdGdJRGeGJ GdeJHGOdI HgOa VeGf GdCef GdTNUj ddOHdheGSjjf dCfg ef ebJVjGJ GdJeKjd GdOHdheGSj Cf jJeJY GdeHYhKhf GdOHdheGSjhf hCaQGO CSQge hOhQ ScfGge hebQ GdHYKI hChQGbgG GdQSejI HGdMQeI hGdMUGfI GddGReJjf MJj jJecfhG ef COGA Yedge GdefhW Hge Ydi Cced hLg(B.s
(3GdeMJhjGJ (B: (3EgOGA(B-(3TcQ hJbOjQ(B-(3ebOeI(B-(3aUd JegjOj (B: (3JWhQ GdMeGjI GdOhdjI ddeHYhKjf GdOHdheGSjjf EHGf GdfRGYGJ GdeSdMI GdOhdjI(B-(3GdHGH GdChd (B: (3bhGYO GdMeGjI GdOhdjI ddeHYhKjf GdOHdheGSjjf EHGf GdfRGYGJ GdeSdMI GdOhdjI, GdaUd GdChd (B: (3GdeYGgOGJ GdOhdjI PGJ GdYdGbGI HGdMeGjI GdOhdjI ddeHYhKjf GdOHdheGSjjf aj CKfGA GdfRGYGJ GdeSdMI GdOhdjI (B...-(3GdHGH GdKGfj (B: (3BdjGJ JfajP GdMeGjI GdOhdjI ddeHYhKjf GdOHdheGSjjf EHGf GdfRGYGJ GdeSdMI GdOhdjI, GdaUd GdChd (B: (3GdBdjGJ GdhWfjI dJfajP MeGjI GdeHYhKjf GdOHdheGSjjf EHGf GdfRGYGJ GdeSdMI GdOhdjI (B...(3hehGVjY CNQi(B.s
(3eUWdMGJ (B: (3UaMI (B543-544.s
(3HHdjhLQGajI (B: (3UaMI (B483-542.s
Keywords: (3GdMUGfI GdOHdheGSjI (B((3bGfhf Ohdj(B)s; (3GdOHdheGSjI (B((3bGfhf Ohdj(B)s; (3GdefGRYGJ GdOhdjIs -- (3bhGfjf hJTQjYGJs